A new species of the genus Sinomastax Yin, 1984 from Qinghai, China (Orthoptera: Eumastacoidea, Eumastacidae) - Li, Xin-Jiang; Zhi, Yong-Chao; Yin, Zhan (Zootaxa, 2025)
A new species of the genus Sinomastax Yin, 1984 collected from Qinghai, China, i.e. Sinomastax qinghaiensis sp. nov. is described in this paper. The new species is similar to Sinomastax longicornea Yin, 1984, but differs from the latter by: antennae of female shorter, not reaching hind margin of pronotum; eye larger, width between lateral carina of pronotum at fore margin narrower than hind margin; subgenital plate of male shorter, apex obtuse; lower ovipositor valve with a big tooth at middle of lower margin. The type specimens are deposited in the School of Life Sciences, Hebei University, Baoding, Hebei.